Social Frailty in the COVID-19 Pandemic Era - Lozupone, Madia; La Montagna, Maddalena; Di Gioia, Ilaria; Sardone, Rodolfo; Resta, Emanuela; Daniele, Antonio; Giannelli, Gianluigi; Bellomo, Antonello; Panza, Francesco (Frontiers in Psychiatry, 2020)
Special attention and efforts to protect from or reduce health-related outcomes of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus causing coronavirus disease 2019 (COVID-19), should be applied in susceptible populations, including frail older people. In particular, the early death cases occurred primarily in older people with a frailty status, possibly due to a weaker immune system fostering faster progression of the viral infection. Frailty is an age-related multidimensional clinical condition defined as a nonspecific state of vulnerability, identifying older people at increased risk of falls, institutionalization, hospitalization, disability, dementia, and death. Among frailty phenotypes, social frailty, taking into account the role played by the socioeconomic context in determining the vulnerability status in older age, has been least studied. COVID-19 does not affect all populations equally, and social inequalities contribute to drive the spread of infections. Subjective social isolation, i.e., loneliness, is associated with poor mental and physical health, but the underlying molecular mechanisms, related to the immune system, and its associated cognitive and health-related sequelae, are poorly understood. The prolonged exposure to stress due to the lockdown scenario may have contributed to an increase in psychological distress by reducing sources of support, and making heavy demands on personal resources. i.e., self-efficacy and relational variables. These issues may have a strong impact on perceived loneliness, a factor associated with psychological distress and an outcome in itself. In the COVID-19 pandemic era, a correct assessment of social frailty may be essential in terms of the prevention of late-life neuropsychiatric disorders.